The Cognitive and Affective Nexus : Critical Thinking, Creativity, Emotional Intelligence, and Academic Success - Syamiya, Estu Niana; Huby, Zindan Baynal; Rosulliaty, Indri (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the direct and indirect effects of critical thinking and creative thinking on academic achievement, with emotional intelligence serving as a mediating variable. A quantitative method employing path analysis was utilized to analyze the relationships between these variables. The population in this study consisted of all students of SMA Al Husna Tangerang City in the academic year 2023/2024, totaling 127 students. Sampling was conducted using the Slovin formula, resulting in a total of 96 students. The results showed that: (1) Critical and creative thinking do not have a significant positive effect on emotional intelligence in students. These results suggest that high levels of critical and creative thinking are associated with stable and improving emotional intelligence. (2) Critical and creative thinking have no significant influence on student academic achievement. These findings indicate that enhancing critical and creative thinking skills can potentially improve student academic achievement. (3) Emotional intelligence has no significant effect on student academic achievement. This highlights the need to enhance students' emotional intelligence to effectively control and regulate emotions.